Uma discussão sobre as densidades de energia em ondas mecânicas unidimensionais - Bruno-Alfonso, Alexys [UNESP]; Florêncio, Alexandro Silveira [UNESP] (Sociedade Brasileira de Física, 2004)
Estudam-se as médias temporais das densidades das energias cinética e potencial em ondas mecânicas unidimensionais. Demonstra-se que o movimento harmônico simples dos elementos do meio não é condição suficiente nem necessária para que aquelas médias sejam iguais. Isso contradiz as abordagens em textos de Halliday et al. e Nussenzveig.

The mean values (in time) of the kinetic and potential energy densities in one-dimensional mechanical waves are studied. It is shown that the simple harmonic motion of the particles is neither a sufficient nor a necessary condition for those mean values to be the same. This contrasts with the approaches in textbooks by Halliday et al. and Nussenzveig.
A discussion on the energy densities in one-dimensional mechanical waves
Keywords: onda mecânica; densidade de energia; valor médio; movimento harmônico simples; mechanical wave; energy density; mean value; simple harmonic motion